Data from Paper ‘Embodied Terror Management: Interpersonal Touch Alleviates Existential Concerns among Individuals with Low Self-esteem’ - Mandy Tjew-A-Sin; Iris Karoline Schneider; Sander Leon Koole (Journal of Open Psychology Data, 2015)
The dataset includes data from the four studies reported in our 'Embodied terror management' paper. The data was collected at either the campus or at the psychology lab at the VU University Amsterdam in 2011/2012 among Dutch-speaking student samples. The dataset consists of the measures described in the paper. The data can be used for replication purposes, meta-analyses, and exploratory analyses, as well as cross-cultural comparisons of mortality salience effects. The authors also welcome collaborative research based on re-analyses of the data.